การพัฒนาแบบทดสอบอัตนัยพหุมิติ / The Development of Multidimensional Essay Test - Rawanprakhon, Pornwimon; Tayraukham, Sombat (Journal of Community Development Research (Humanities and Social Sciences); Vol 10 No 4 (2560): October-December 2017, 2017)
แบบทดสอบอัตนัยเป็นแบบทดสอบที่สามารถวัดพฤติกรรมระดับสูงได้ดี โดยผู้ตอบแสดงความคิดของตนเองได้อย่างอิสระด้วยประสบการณ์และความรู้ที่มีอยู่ แต่มีข้อจำกัดที่ไม่สามารถสร้างได้ครอบคลุมเนื้อหาเนื่องจากหนึ่งข้อวัดได้เพียงหนึ่งมิติ แนวทางแก้ไขจึงใช้ทฤษฏีโมเดลการตอบสนองข้อสอบพหุมิติ (Multidimensional Item Response Theory: MIRT) ซึ่งมีลักษณะโครงสร้างเป็นองค์ประกอบเชิงซ้อนที่จะช่วยลดข้อคำถามให้น้อยลงแต่ถามได้ครอบคลุมมากขึ้น ด้วยเหตุนี้ บทความนี้จึงมีวัตถุประสงค์เพื่อนำเสนอแนวคิดการพัฒนาแบบทดสอบอัตนัยพหุมิติโดยใช้การคิดอภิมานเป็น ตัวแบบในการสร้าง ซึ่งมีขั้นตอนในการพัฒนาดังนี้ คือ การกำหนดจุดมุ่งหมายของข้อสอบ การกำหนดนิยามเชิงปฏิบัติการของการคิดอภิมาน การกำหนดโมเดลการวัดความสามารถการคิดอภิมานมีลักษณะเป็นพหุมิติภายในข้อคำถาม (Within–Items Multidimensionality) การสร้างข้อสอบและการหาคุณภาพข้อสอบ ซึ่งประกอบด้วย ความตรงเชิงเนื้อหา ความตรงเชิงโครงสร้าง ค่าอำนาจจำแนก ค่าความยาก และความเชื่อมั่นแบบพหุมิติ จากนั้นประมาณค่าความสามารถการคิดอภิมานของผู้สอบแล้วรวมค่าความสามารถแยกเป็นด้านๆ จะทำให้ทราบว่าบุคคลนั้นมีความสามารถโดดเด่นหรือด้อยด้านใด อันจะเป็นสารสนเทศที่เป็นประโยชน์ต่อผู้เรียนในการพัฒนาตนเอง และต่อครูในการพัฒนากิจกรรมการเรียนการสอนให้สอดคล้องกับผู้เรียนยิ่งขึ้น      The essay test is a test that can measure well on high-level behavior because respondents can share their own ideas freely with existing experiences and knowledges. However, it can-not be made to cover the content, since one item measures only one dimension. One solution is using the Multidimensional Item Response Theory (MIRT), which is structured as a complex component, reducing the number of questions, but more comprehensive. Therefore, the purpose of this article was to present the concept of developing Multidimensional Essay Test using metacognition as a model. The developing procedures were as follows: setting the purpose of the test, defining operational definition of metacognition, defining a multidimensional within-items model, test construction, and test properties including content validity, construct validity, item discrimination, item difficulty, and a test reliability. Then, their abilities are estimated and combined in each element to determine whether they have outstanding abilities or not. The outcome from this study would be beneficial for learners and teachers.
Keywords: การคิดอภิมาน, แบบทดสอบอัตนัย, ทฤษฏีการตอบสนองข้อสอบแบบพหุมิติ, คุณภาพข้อสอบอัตนัยแบบพหุมิติ Metacognition, Essay Test, Multidimensional Item Response Theory (MIRT), Quality of Multidimensional Essay Test